A state-of-the-art review of distribution-of-practice effects on L2 learning - Serrano, Raquel (Studies in Second Language Learning and Teaching, 2022)
The purpose of this state-of-the-art review is to provide a general overview of recent research on time distribution and second language (L2) learning with special implications for classroom settings. Several studies have been performed to examine how to best distribute the hours of L2 practice to maximize learning by comparing conditions that promote intensive exposure versus others in which L2 input or instruction is more widely spaced. Findings from these studies are relevant not only for practical purposes but also for theory development. This review provides a summary of recent studies as well as suggestions for pedagogical practice. Additionally, it identifies areas for future research concerning the effect of time distribution on L2 learning.